Relevance of Corporate Social Responsibility (CSR) for Latin American Entrepreneurs - Winfried Polte (Hochschule Bonn-Rhein-Sieg, Internationales Zentrum für Nachhaltige Entwicklung (IZNE), 2017)
These times are very troubled ones. Not only do wars and political unrest seem to prevail in different regions of the world, but, corruption and fraud have reached an incredible dimension, too. It seems that societies have, to a large extent, lost values in which they had formerly believed in. These issues may be the background why at the moment Corporate Social Responsibility (CSR) as a voluntary commitment is discussed in public that intensively. However, one gets the impression that this rather often seems to be superficial. Therefore, it is time to do some in-depth research to identify whether there is real substance behind these discussions or not. Latin America is a big continent with a greater number of countries which are running through difficult times as to corruption and fraud. Consequently, the author studied the policy of the central employers association Consejo Empresarial de America Latina (CEAL) with respect to the role of CSR. On the basis of statements, news and results of studies being regularly published, conclusions were drawn to which extent social and environmental aspects, along the line of ISO 26000, are playing a relevant role. In order to avoid a too narrow view of the issue, a holistic approach concerning the general situation of Latin America has been selected using parameters such as economic growth, increase of population, poverty, inequality, and the global responsibility for environment. Furthermore, apart from the central organization CEAL, regional and national institutions with a specific mission for spreading and implementing CSR and two communal projects were analyzed as well. The conclusion of the paper is that there are some CSR 'lighthouses' but an urgent need exists to spread the idea of CSR more intensively across the continent. Corresponding recommendations about how to increase the relevance of CSR in Latin America are given at the end of the paper.
urn:nbn:de:hbz:1044-opus-31800
Keywords: M14; 330; CSR; Corporate Social Responsibility; Entrepreneurship; Latin America